Sources and formation pathways of organic aerosol in a subtropical metropolis during summer. (September 2015) - Tsai, I-Chun; Chen, Jen-Ping; Lung, Candice Shi-Chun; Li, Nan; Chen, Wei-Nai; Fu, Tzung-May; Chang, Chih-Chung; Hwang, Gong-Do
Abstract: A field campaign combined with numerical simulations was designed to better understand the emission sources and formation processes of organic aerosols (OA) in a subtropical environment. The field campaign measured total and water soluble organic carbon (OC) in aerosol, as well as its precursor gases in the Taipei metropolis and a nearby rural forest during the summer of 2011. A regional air-quality model modified with an additional secondary organic aerosol (SOA) formation pathway was used to decipher the observed variations in OA, with focus on various formation pathways and the relative contributions from anthropogenic and biogenic sources. According to the simulations, biogenic sources contributed to 60% and 72% of total OA production at the NTU (urban) and HL (rural) sites. The simulated fractions of SOA in total OA were 67% and 79% near the surface of NTU and HL, respectively, and these fractions increased with height and reach over 90% at the 1-km altitude. Estimated from the simulation results, aqueous-phase dicarbonyl uptake was responsible of 51% of OA production in the urban area, while the primary emissions, reversible partitioning of semi-volatile oxidation products, oligomerization of semi-volatile SOA in the particulate phase and acid-enhanced oxidation contributed to 33%, 10%, 5% and 1% respectively; in the rural area, the percentages were 59%, 21%, 13%, 7% and 1%, respectively. Meteorological factors, including large-scale wind direction, local circulation and planetary boundary layer height, all have strong influences on the source contributions and diurnal variations of OA concentration. Highlights: Biogenic contributions to OA formation are strong in both urban and rural Taipei. SOA dominated OA production, and its fraction increases with height in the PBL. Major contribution of OA from aqueous-phase processes. PBL height & sunlight variations and local circulation controlled OA diurnal cycle.